Breast Feeding: knowledge and practice of pregnancy - da Mota Santana, Jerusa; Monteiro Brito, Sheila; Barbosa dos Santos, Djanilson (O Mundo da Saúde, 2013)
Breastfeeding contributes positively to the growth and development of children and presents advantages immunological, psychological and nutritional. Additionally, it leads to considerable reduction in mortality from all causes and is also important for women’s health. Considering the information presented, there is the objective of this study was to identify the knowledge and practice of breast-feeding of pregnant women attending health facilities in one district of Reconcavo Baiano. It is a cross-sectional study involving pregnant women attending antenatal care in health facilities in the municipality Reconcavo of Bahia, October/2010 to May/2011. The study excluded women with HIV / AIDS or who refused to participate. We used a structured questionnaire on breastfeeding and breastfeeding technique, containing 34 questions, 19 aimed at multiparous on previous experience with breastfeeding. We interviewed 50 pregnant women, 68% primiparous. About 76% of women felt that children should breastfeed exclusively breastfed until 6 months, and 80% considered strong breast milk. Regarding the benefits of breastfeeding for the health of women, 88% recognized the importance of this practice and pointed as the main benefit to reducing breast cancer (68%). Although most mothers present knowledge about the importance of breastfeeding, it is not yet satisfactorily applied in the practice of breastfeeding. Must stress the importance of education initiatives and support breastfeeding from antenatal and even the phase of introduction of new foods for optimal breastfeeding.